2002
DOI: 10.1007/s00018-002-8454-2
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein: the multipurpose protein

Abstract: Metallothioneins (MTs) are intracellular, low molecular, low molecular weight, cysteine-rich proteins. Ubiquitous in eukaryotes, MTs have unique structural characteristics to give potent metal-binding and redox capabilities. A primary role has not been identified, and remains elusive, as further functions continue to be discovered. The most widely expressed isoforms in mammals, MT-1 and MT-2, are rapidly induced in the liver by a wide range of metals, drugs and inflammatory mediators. In teh gut and pancreas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
815
1
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,159 publications
(842 citation statements)
references
References 248 publications
10
815
1
16
Order By: Relevance
“…45 These Cu and Zn-binding proteins are strictly involved in Zn homeostasis and have been related to Zn absorption. 46 Here, we did not find metallothionein over-expression in IB3-1 cells. However, the up-regulation of metallothioneins in response to increased oxidative stress 30 could be related to the observed increases of intracellular Zn and Cu.…”
Section: Paper Molecular Biosystemscontrasting
confidence: 52%
“…45 These Cu and Zn-binding proteins are strictly involved in Zn homeostasis and have been related to Zn absorption. 46 Here, we did not find metallothionein over-expression in IB3-1 cells. However, the up-regulation of metallothioneins in response to increased oxidative stress 30 could be related to the observed increases of intracellular Zn and Cu.…”
Section: Paper Molecular Biosystemscontrasting
confidence: 52%
“…MT induction is known to be transcriptionally regulated by different stimuli including metals, glucocorticoids and oxidative stress (Coyle et al, 2002). The zinc finger metal transcription factor-1 (MTF1) modulates MT induction by binding to specific cis-acting promoter elements (Andrews 2000; Bury et al, 2008).…”
Section: Gene Expressionmentioning
confidence: 99%
“…Plant MTs are 20 further subdivided into several types (type 1, 2, 3 and 4) according to the distribution of Cys residues (Cobbett et al 2002). In animals, MTs are i nvolved in metal 5 homeostasis and scavenging of reactive oxygen species (Thornalley & Vasak 1985;Palmiter 1998;Suhy et al 1999;Coyle et al 2002). It is also worth noting that many studies have demonstrated that there is a tight correlation between the expression of MT genes and many important physiological processes, such as aging (Yang et al 2006) and cell apoptosis (Raymond et al 2010).…”
Section: Introductionmentioning
confidence: 99%